Na/K-ATPase Signaling and Salt Sensitivity: The Role of Oxidative Stress - Jiang Liu; Yanling Yan; Ying Nie; Joseph I. Shapiro (MDPI AG, 2017)
Other than genetic regulation of salt sensitivity of blood pressure, many factors have been shown to regulate renal sodium handling which contributes to long-term blood pressure regulation and have been extensively reviewed. Here we present our progress on the Na/K-ATPase signaling mediated sodium reabsorption in renal proximal tubules, from cardiotonic steroids-mediated to reactive oxygen species (ROS)-mediated Na/K-ATPase signaling that contributes to experimental salt sensitivity.